PENGARUH PENAMBAHAN BUAH NAGA MERAH (Hylocereus polyrhizus) TERHADAP MUTU PERMEN KARAMEL SUSU - Marlina, Marlina; Wijaya, Mohammad; Kadirman, Kadirman (Jurnal Pendidikan Teknologi Pertanian, 2019)
This study aims to determine the effect of adding red dragon fruit to the chemical and hedonic content of caramel milk. This study used a method of adding 20%, 30%, and 40% red dragon fruit pulp for caramel milk candy with a cooking time of 2 hours at 80ËšC. This research is a quantitative study (experiment) using a completely randomized design (CRD) with 4 treatments, each control, 20%, 30%, and 40% with 3 replications. The research data was obtained from the results of chemical testing (moisture content, ash content, fiber, reduction sugar, and antioxidants) and organoleptic (color, taste, aroma, and texture), data were analyzed using analysis of variance (ANOVA) and continued with DRMT test (Duncan ) at a 95% confidence level. The results showed that the addition of red dragon fruit pulp had an effect on caramel milk candy, the best research on the manufacture of caramel milk was the addition of 40% red dragon fruit pulp with characteristics of 3.54% moisture content, 1.98% ash content, 1.48% fiber content, decreased sugar content 2.18%, antioxidant content 53.77%, favorite color value 4.10, favorite aroma value 3.52, flavor 3.83, and favorite texture value 3.23